2007
DOI: 10.1099/mic.0.2006/004275-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the aerobactin and ferric hydroxamate uptake systems of Yersinia pestis

Abstract: Yersinia pestis genomes contain genes homologous to the aerobactin receptor (iutA) and biosynthetic genes (iucABCD) as well as the ferric hydroxamate uptake system (fhuCDB) of Escherichia coli. However, iucA is disrupted by a frameshift mutation. An E. coli strain carrying the cloned Y. pestis aerobactin region was unable to produce aerobactin, but could use the siderophore as an iron source. Repair of the frameshift mutation in iucA did not allow aerobactin production in E. coli or Y. pestis. In contrast, a Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 52 publications
4
40
0
Order By: Relevance
“…To investigate the involvement of FhuD in the growth defect of the tatC mutant at 37°C and to look into the Tat dependency of FhuD export, we also investigated the growth of these strains in iron-limited medium containing ferrichrome. FhuD functions in the uptake of ferric-hydroxamate-type ferrichrome, which is an iron-chelating siderophore (28). As a control, we also included a ⌬ybtP mutant, as ybtP is a gene required for another independent iron uptake system.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the involvement of FhuD in the growth defect of the tatC mutant at 37°C and to look into the Tat dependency of FhuD export, we also investigated the growth of these strains in iron-limited medium containing ferrichrome. FhuD functions in the uptake of ferric-hydroxamate-type ferrichrome, which is an iron-chelating siderophore (28). As a control, we also included a ⌬ybtP mutant, as ybtP is a gene required for another independent iron uptake system.…”
Section: Resultsmentioning
confidence: 99%
“…We have found that C. difficile encodes a putative Fhu (ferric hydroxamate uptake) ABC transporter system which is expressed under iron-limiting conditions and is repressed by Fur. Fhu transporters have been shown to function in iron acquisition in many Gram-positive as well as Gram-negative bacteria (31)(32)(33)(34). C. difficile also encodes a system homologous to the catecholate siderophore petrobactin ABC transporter Fpi/Ycl from B. subtilis (35).…”
Section: Discussionmentioning
confidence: 99%
“…Construction of potentially virulent strains and virulence testing were performed in a CDC-approved biosafety level 3 (BSL3) laboratory following select agent regulations, using procedures approved by the University of Kentucky Institutional Biosafety Committee. Y. pestis strains were transformed with the virulence plasmid pCD1Ap by electroporation (43,45) and plated on TBA plates containing Ap (50 g/ml). The plasmid profile of transformants was analyzed, as well as their phenotype on CR agar (88) and magnesium-oxalate plates (48).…”
Section: Methodsmentioning
confidence: 99%